Weight cycling induces innate immune memory in adipose tissue macrophages - Caslin, Heather L.; Cottam, Matthew A.; Piñon, Jacqueline M.; Boney, Likem Y.; Hasty, Alyssa H. (Frontiers in Immunology, 2023)
Introduction Weight loss improves obesity-associated diabetes risk. However, most individuals regain weight, which worsens the risk of developing diabetes and cardiovascular disease. We previously reported that male mice retain obesity-associated immunological changes even after weight loss, suggesting that immune cells may remember the state of obesity. Therefore, we hypothesized that cycles of weight gain and loss, otherwise known as weight cycling, can induce innate memory in adipose macrophages. Methods Bone marrow derived macrophages were primed with palmitic acid or adipose tissue conditioned media in a culture model of innate immune memory. Mice also put on low fat or high fat diets over 14-27 weeks to induce weight gain, weight loss, and weight cycling. Results Priming cells with palmitic acid or adipose tissue conditioned media from obese mice increased maximal glycolysis and oxidative phosphorylation and increased LPS-induced TNFα and IL-6 production. Palmitic acid effects were dependent on TLR4 and impaired by methyltransferase inhibition and AMPK activation. While weight loss improved glucose tolerance in mice, adipose macrophages were primed for greater activation to subsequent stimulation by LPS ex vivo as measured by cytokine production. In the model of weight cycling, adipose macrophages had elevated metabolism and secreted higher levels of basal TNFα, suggesting that weight loss can also prime macrophages for heighted activation to weight regain. Discussion Together, these data suggest that weight loss following obesity can prime adipose macrophages for enhanced inflammation upon weight regain. This innate immune memory response may contribute to worsened glucose tolerance following weight cycling.